DIALOG ESOTERIS ANTARAGAMA: Kajian Filsafat Iluminasi Suhrawardi - Arifinsyah Arifinsyah (State Islamic University North Sumatra, 2008)
Abstract: Interreligious Esoteric Dialogue: A Study of Suhrawardi’s Illuminative Philosophy. A sufi is one of the most serius figures who deals and gets involved with the esoteric interfaith dialogue related not only to academic discourses but also to practical aspects. One of well-known sufi is Suhrawardi, a pioneer of the illumination philosophy, who succeed to combine between profane and sufistic or esoteric dimension into a religious life. The writing tries to analyze Suhrawardi’s opinions concerning the esoteric dialogue among religious adherents. Kata Kunci: dialog esoteris, agama-agama, dan iluminatif